2021
DOI: 10.52628/87.4.28
|View full text |Cite
|
Sign up to set email alerts
|

Dynesys® dynamic stabilization outcomes in degenerative spine surgery

Abstract: Dynesys® is a dynamic device used for posterior stabilization of the lumbar spine. The objective of this study was to analyze the clinical and radiological outcomes at a 2-year minimum follow-up. In this retrospective study, patients operated between 2009 and 2016 with Dynesys® stabilization were in- cluded. 5 different etiologies were included: disc herniation, lumbar stenosis, revision for adjacent seg- ment disease (ASD), spondylolisthesis, and scoliosis. Clinical and radiological evaluations were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…In our cohort, the rate of PJK was 3%, which is much lower than that reported in the literature. Interestingly, the average blood loss (611.7 mL) in our study was much higher than that reported by Hsieh et al [24] (250 mL) and Yang et al [25] (386 mL) but similar to that reported by Khalife et al [26] (736 mL).…”
Section: Discussionsupporting
confidence: 86%
“…In our cohort, the rate of PJK was 3%, which is much lower than that reported in the literature. Interestingly, the average blood loss (611.7 mL) in our study was much higher than that reported by Hsieh et al [24] (250 mL) and Yang et al [25] (386 mL) but similar to that reported by Khalife et al [26] (736 mL).…”
Section: Discussionsupporting
confidence: 86%
“…The Dynesys (Zimmer Biomet) was first developed for the treatment of degenerative spine conditions in adult patients 17 . This tether was used to provide dynamic stabilization in the treatment of spondylolisthesis, disk herniations, spinal stenosis, adjacent segment disease, and pseudarthrosis 17,18 . Junctional tethers have been used at the cranial aspect of long posterior instrumented constructs to distribute proximal motion segment stiffness and reduce proximal junctional kyphosis 19 .…”
Section: Methodsmentioning
confidence: 99%
“…17 This tether was used to provide dynamic stabilization in the treatment of spondylolisthesis, disk herniations, spinal stenosis, adjacent segment disease, and pseudarthrosis. 17,18 Junctional tethers have been used at the cranial aspect of long posterior instrumented constructs to distribute proximal motion segment stiffness and reduce proximal junctional kyphosis. 19 While this device has fallen out of favor for adult patients, 17 the device was implanted according to physician-directed use for VBT until it was removed from the US market in 2019.…”
Section: Initial Development Of Vbtmentioning
confidence: 99%
“…It could theoretically preserve the mobility of the operated segment and lessen the pressure on the adjacent discs and facet joints (9), which means that it can be installed in middle-aged patients with single-or multi-segmental LDD. Some studies have supported the purported bene cial effect of Dynesys in preserving range of motion (ROM) and preventing ASD in LDD patients (10)(11)(12)(13). Other studies refuted the claim and demonstrated that Dynesys failed to achieve that bene cial effect (14).…”
mentioning
confidence: 99%